(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
A condition of acquired macular depigmentation called vitiligo is linked to melanocyte degeneration, caused by the autoimmune destruction of melanocytes cells. This vitiligo can be correlated to Shwitra in Ayurveda because of the disease’s resemblance in appearance. In the Ayurveda classics especially Charaka Samhita, Shwitra has been mentioned under the heading of Kushta Roga Chikitsa. Methodology: The present case report is of 11 years old female child, came with complaints of whitish discolored patches on the almost all over body, effectively treated with Shamana and Shodhana Chikitsa. Result: Patient showed encouraging result after Shodhana Chikitsa, where subjective criteria evaluated using scoring method and objective criteria evaluated using VASI scoring method. Discussion: Patient was treated with Shamana Aushadis and Shodhana, where white discolored patches turned to pinkish, and after that the patches turned into normal skin color. Subject was observed with 95% improvement in subjective criteria & VASI scoring improved from 19.85 to 3.2. Conclusion: The present case study validated the efficacy of Ayurveda medicine in treating Shwitra.